2016
DOI: 10.1002/cjoc.201600226
|View full text |Cite
|
Sign up to set email alerts
|

Origin of d‐π Interaction in Cobalt(II) Porphyrins under Synergistic Effects of Core Contraction and Axial Ligation: Implications for a Ligand Effect of Natural Distorted Tetrapyrrole

Abstract: The reactivity of the metalloporphyrins was closely related to their ligand effect at axial position. The electronic properties of six model Co(II) porphyrins are investigated by spectral and electrochemical methods. Structural parameters of the Co(II) complexes are directly obtained from their crystal structures. We demonstrate that the unpaired 3d electron of low‐spin Co(II) ions in nonplanar Co(II) porphyrin complexes activated by core contraction of porphyrin macrocycles can be further activated by the axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…An inspection of the plot shows that the structures of the three metal ions in the model porphyrins can be changed and their diameters are mutually independent of each other. It has been shown that changing the macrocycle core size can directly change the electronic structures of iron(III), and cobalt(II) , . A similar effect is seen for nickel(II); the conversion point is between n C = 4 and 5 (Figure , labeled ☆), which is in agreement with the position derived from the spectral deviation (Figure ).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…An inspection of the plot shows that the structures of the three metal ions in the model porphyrins can be changed and their diameters are mutually independent of each other. It has been shown that changing the macrocycle core size can directly change the electronic structures of iron(III), and cobalt(II) , . A similar effect is seen for nickel(II); the conversion point is between n C = 4 and 5 (Figure , labeled ☆), which is in agreement with the position derived from the spectral deviation (Figure ).…”
Section: Resultssupporting
confidence: 75%
“…Figure shows that only the curve for the iron series crosses that of the metal‐free one, and the other two slightly cross or drift away from it; even the largest core, containing nickel(II), is just close to the lowest limiting free‐metal core value. The results also imply that porphyrin distortion can be affected by the size of the central ion as well as stretching of alkyl bridges and crowding of peripheral groups in synthetic nonplanar porphyrins. In the current model series, the small nickel(II) [or cobalt(II)] ion slightly increases the degree of distortion, as shown by the fact that the L N1N3 values are shorter in the metal‐containing series than in the metal‐free one and the A mC values are larger in the former than in the latter (Table ).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations